EXPLORING THE POTENTIAL OF EDUCATIONAL ANDROID GAMES FOR PROSPECTIVE ELEMENTARY SCHOOL TEACHERS: A RESPONSE - Ibrahim Ibrahim; Nurwahidah Nurwahidah; Ni Made Yeni Suranti; Nurkhaerat Alimuddin (JGK (Jurnal Guru Kita), 2024)
This research aims to explore the responses of prospective elementary school teachers to training in developing Android-based educational games as an innovative learning tool. By distributing questionnaires to 121 prospective elementary school teachers in NTB, this research identified the needs, interests, motivations and challenges faced in participating in the training. The research results show that prospective elementary school teachers show a high interest in using educational games as a learning tool, but prospective elementary school teachers face challenges related to technical skills and integration in the curriculum. These findings provide important insights for training providers in designing programs that better suit the needs of prospective teachers, as well as highlighting the importance of continued support for the development of skills in using technology in education.